A multistage hydatic cyst case with multicentric localizatioın and transdiaphragmatic invasion - Deveci, Figen; Turgut, Tevfik; Muz, Mehmet Hamdi; Akfırat, Murat; Çekirdekçi, Ahmet (My University, 2002)
A 29-year-old female patient presented with intermittent left shoulder pain that had been present for nearly two years. The patient had been operated for a hydatic cyst six years ago. PA lung X-rays yielded homogeneous radio opacity in the left middle and lower lobes. With the help of further radiological investigations, the patient was diagnosed as a case of multistage hydatic cyst with multiple localization and transdiaphragmatic invasion. (A surgical intervention was performed by the staff of the Department of Thorax and Cardiovascular Surgery). The cysts were excised with cystotomy and capitonnage. The diaphragm was also found to be attacked by the cysts and was primarily repaired by capitonating the cyst walls and the cysts above and under the diaphragm were excised. Albendazole was started in a dose of 10 mg/kg(day. The patient had an uneventful recovery.
Keywords: Adult; Tomography; X-Ray Computed; Case report; Diaphragm; Echinococcosis; Treatment Outcome; Surgical Procedures; Operative; Hydatid cyst